Stride toward freedom the Montgomery story. - King, Martin Luther Jr. 1929-1968. (New York Harper, 1958)
Chronicles the Montgomery, Alabama bus boycott sparked by Mrs. Rosa Parks' refusal to give up her seat to a white male, describing the plans and problems of a nonviolent campaign, reprisals by the white community, and the eventual attainment of desegregated city bus service.
Keywords: Segregation in transportation -- Alabama -- Montgomery; African Americans -- Alabama -- Montgomery; Segregation in transportation -- Alabama -- Montgomery; Afro-Americans -- Alabama -- Montgomery; Montgomery (Ala.) -- Race relations; Montgomery (Ala.) -- Race relations